2001
DOI: 10.1159/000054909
|View full text |Cite
|
Sign up to set email alerts
|

Season of Birth Variations in the Temperament and Character Inventory of Personality in a General Population

Abstract: Background: Since several studies show season of birth variations in morbidity, suicidal behavior and CSF (cerebrospinal fluid) monoamine metabolites, we investigated season of birth variations in personality in the population. Methods: We analyzed by multiple logistic regressions the Temperament and Character Inventory (TCI) for 2,130 individuals taking part in the Betula prospective random cohort study of Umeå, Sweden. Results: The personality dimensions were correlated significantly with age and gender. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 55 publications
1
37
2
2
Order By: Relevance
“…The first two columns of table 3 display the results of similar analyses as above for other birth seasons. The pair of birth seasons compared in the first column (February to April vs. the remaining year), and in the second column (October to January vs. the remaining year) are the ones that have been studied in the context of season of birth associations with CSF monoamine metabolites [12], suicide methods [13,14], and personality scales [15]. Here, the birth season February to April did not show any essential association with morningness-eveningness preference.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The first two columns of table 3 display the results of similar analyses as above for other birth seasons. The pair of birth seasons compared in the first column (February to April vs. the remaining year), and in the second column (October to January vs. the remaining year) are the ones that have been studied in the context of season of birth associations with CSF monoamine metabolites [12], suicide methods [13,14], and personality scales [15]. Here, the birth season February to April did not show any essential association with morningness-eveningness preference.…”
Section: Resultsmentioning
confidence: 80%
“…These include season of birth variations in monoamine neurotransmitter turnover [12], in suicidal behavior [13,14], and in personality [15]. In those studies, the birth season October to January was associated, respectively, with higher cerebrospinal fluid (CSF) levels of the dopamine metabolite homovanillic acid and the serotonin metabolite 5-hydroxyindoleacetic acid, with the choice of the suicide method poisoning or petrol gases rather than hanging, and with the personality dimension of low novelty seeking among women and of low persistence among men.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, individuals who reported lower parental care and higher parental intrusiveness were more likely to be higher in neuroticism, lower in conscientiousness, lower in SD and higher in HD. 129 Other examples of environmental variables that have been reported to affect personality include season of birth 130,131 and childhood sexual abuse. 132,133 A multidisciplinary approach in which geneticists and epidemiologists join a collaborative effort could uncover some of the important genetic and environmental variables and the possible gene-environment interactions.…”
Section: Multiple Testingmentioning
confidence: 99%
“…Previous research has reported a statistically significant influence of season of birth on factors such as brain tumour development 1 , handedness 2 , longevity 3 , personality 4 , and schizophrenia and bipolar disorder 5 . Does season of birth also have an influence on mood?…”
Section: Introductionmentioning
confidence: 99%